Results of graduate follow-up and qualitative evaluation of the physical education, sports and recreation career, ULEAM, Manta, Ecuador (Review) (Revista científica Olimpia, 2019)
Tracking the graduate is the most important tool for the continuous improvement of the training process of career professionals. In the present article a study of the cohorts 2010, 2011 and 2012 in the Graduate Follow-up Area is made in the confrontation of professional competencies and the degree to which they are required in their job (fields of action and areas of performance), of the Physical Education, Sports and Recreation career of the Laica Eloy Alfaro de Manabí University (ULEAM), Manta, Ecuador, with the survey named: 007 - Physical Education, Sports and Recreation - Graduation Profile - Beta, with the objective of implementing improvements in academic programs and maintaining a balance between professional competencies and the demands of the work environment through appropriate curricular adjustments. Therefore, it is of vital importance in evaluating the career and quality of its graduates and the relevance of their training. The results showed some deficiencies in the competences acquired and in the need to evaluate and modify the contents of some subjects that enable them for their professional performance.
Keywords: evaluation; relevance; satisfaction; employability; graduation profile